CAN AI HELP US TELL THE TRUTH ABOUT FOOD? - Magdalena Bednjanec; Siniša Jovčić; Dean Nižetić (Faculty of Social and Political Sciences, Universitas Lampung, 2025)
Misinformation related to food and nutrition is increasingly prevalent on the internet, contributing to public confusion, poor dietary habits and a decline in trust in credible health sources. The aim of this study is to investigate how existing artificial intelligence (AI) tools - such as language models, search engines with AI ranking systems and browser-based fact-checking plugins - influence public awareness and decision-making regarding food and nutrition information. The study uses a mixed methods approach that combines a survey to assess user habits and trust in AI tools with a qualitative analysis of AI-generated content and fact-checking results related to common food myths. The research is based on theories of media literacy and digital trust and provides a framework for understanding how users evaluate the credibility of information in AI-mediated environments. Key findings show that while AI tools are widely used to access health-related information, many users are unaware of how these systems work, resulting in mixed levels of trust and varying effectiveness in discerning reliable content. In addition, users expressed uncertainty about the transparency and accuracy of AI-driven fact-checking mechanisms. Based on the findings, this study recommends the development of clearer strategies to educate users, increased transparency of AI platforms, and policies to promote digital literacy as a means to support food security through informed decision-making. These findings emphasize the role of existing AI technologies not just as tools, but as influential facilitators of public understanding of nutrition and health.